A Tongue in the Mouth of the Dying - Guerrero, Laurie Ann (Book collections on Project MUSE., 2013)
Filled with the beauty and complexity of the everyday - a pot of beans, a goat carcass, embroidered linens, a grandfather's cancer - the author journeys through the inherited fear of creation and destruction. The histories of South Texas and its people unfold, including the dehumanization of men and its consequences on women and children. The tongue becomes a palpable border, occupying those liminal spaces that both unite and divide, inviting readers to consider that which is known and unknown: the body. The author explores not just the right, but the ability to speak and fight for oneself, one's children, one's community - in poems that testify how, too often, we fail to see the power reflected in the mirror.--adapted from publisher's description.